O4.6. HERITABILITY OF SPECIFIC COGNITIVE FUNCTIONS AND ASSOCIATIONS WITH SCHIZOPHRENIA SPECTRUM DISORDERS USING CANTAB: A NATION-WIDE TWIN STUDY. (9th April 2019) - Lemvigh, Cecilie; Brouwer, Rachel; Pantelis, Christos; Hilker, Rikke; Robbins, Trevor W; Sahakian, Barbara; Glenthoj, Birte; Fagerlund, Birgitte
Abstract: Background: Many cognitive functions are under strong genetic control and especially measures of intelligence (IQ) have shown high heritability estimates. Schizophrenia is a highly heritable illness associated with widespread cognitive deficits. Twin studies have reported genetic overlap between schizophrenia and intelligence as well as some aspects of memory and executive functioning. How the genetic relationship between specific cognitive functions and schizophrenia is influenced by IQ is currently unknown. Methods: Twin pairs concordant or discordant for a diagnosis in the schizophrenia spectrum were recruited by linking The Danish Twin Register and The Danish Psychiatric Central Research Register. For the present study a total of 214 twins were included: 32 complete monozygotic (MZ) and 22 complete dizygotic (DZ) proband pairs and 29 complete MZ and 20 complete DZ healthy control pairs. In addition, eight twins from proband pairs were included without their sibling. Specific cognitive functions were examined using selected tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB), four subtests from Wechsler's Adult Intelligence Scale (WAIS-III) (Vocabulary, Similarities, Matrix Reasoning & Block Design) and the Danish version of the National Adult Reading Test (DART). A principal component analysis of the CANTAB measures resulted in seven factors (Planning/spatial span, Self-ordered spatial working memory, Sustained attention, Movement time, Set-shifting, Reflection impulsivity, and Thinking time). IQ tests were divided into estimated verbal and performance IQ. Structural equation modelling was applied to quantify the genetic and environmental contributions to the variability of the specific cognitive functions and to examine associations with schizophrenia liability. Results: Genetic factors contributed significantly to Planning/spatial span (25%), Self-ordered spatial working memory (64%), Sustained attention (56%), and Movement time (47%), whereas only unique environmental factors contributed significantly to Set-shifting, Reflection impulsivity, and Thinking time. Genetic factors also significantly explained the variance in verbal (86%) and performance IQ (52%). Schizophrenia liability was significantly associated with Planning/spatial span (rph = -0.34), Self-ordered spatial working memory (rph = -0.24), Sustained attention (rph = -0.23), and Set-shifting (rph = -0.21). For the first two of the above factors genetic covariance accounted for the observed associations. The genetic overlap between Planning/spatial span and schizophrenia was not shared with either performance or verbal IQ. The remaining covariances were shared with performance, but not verbal IQ. Discussion: Specific cognitive functions measured by the CANTAB as well as measures of intelligence were heritable, providing further evidence that cognitive performance is influenced by genetics. Furthermore, four of the seven CANTAB factors were associated with schizophrenia liability, suggesting a partially shared etiology. Only Planning/spatial span was linked to schizophrenia through a genetic pathway separate from both performance and verbal IQ, indicating that this CANTAB factor could be an endophenotype for schizophrenia independent of IQ.